ANALISIS FAKTOR RISIKO KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BALITA DI WILAYAH KERJA UPT. PUSKESMAS MENGWI III TAHUN 2016 - Darmawan, I Gde Arya Dhioxa; Sutarga, I Made (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021DO - 10.24843/ACH.2021.v08.i03.p05, 2022)
ABSTRACT ARI’s an acute disease that can lead toddlers to risk of death. Some risk factors for ARI in toddlers are gender, immunization status, nutritional status, physical condition of the home, toddler mother education and family behavior. This study aims to determine what risk factors affect the incidence of ARI on toddlers in UPT. Puskesmas Mengwi III Badung Bali. This study uses matched pair case-control study design. Toddlers whose roof types did not meet the requirements 2 times more risk to get ARI. Toddlers with families who use anti-mosquito coils 3 times more risk to get ARI. Toddlers with families who use firewood for cooking are 7 times more risk to get ARI. Risk factors for ARI on toddlers in there is a types of roof that doesn’t meet the requirements, the use of anti-mosquito coils, and the use firewood in cooking activities by family. Keywords: ARI, Toddlers, Risk Factors.